2021
DOI: 10.3928/01477447-20201216-03
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Free Arthroscopic Rotator Cuff Repair

Abstract: Rotator cuff repair is known to cause significant pain, and therefore opioids are often prescribed postoperatively. The United States is currently experiencing an opioid epidemic, and prescription opioids are considered a gateway drug to opioid abuse and addiction. Orthopedic surgeons are looking for alternative means to control pain. The purpose of this study was to evaluate the efficacy of an opioid-free postoperative pain protocol in patients following an arthroscopic rotator cuff repair. A prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One prospective studies found that 67% of patients were able to complete opioid-free ARCR when undergoing multimodal pain regimen, including premedication, interscalene nerve block, intraoperative injection, and ketorolac, zolpidem, and acetaminophen at discharge. 40 A randomized controlled trial found that whereas a nonopioid group had significantly greater VAS pain on postoperative days 1 and 4 after ARCR, the nonopioid group actually demonstrated significantly lower VAS pain and pain intensity at every time point (P \ .01) when accounting for confounding factors. 17 Moutzouros et al 26 found that 45% of patients were able to complete nonopioid postoperative protocols when enrolling patients undergoing a wide range of sports orthopaedics procedures, including anterior cruciate ligament reconstruction, ARCR, labral repair, and meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One prospective studies found that 67% of patients were able to complete opioid-free ARCR when undergoing multimodal pain regimen, including premedication, interscalene nerve block, intraoperative injection, and ketorolac, zolpidem, and acetaminophen at discharge. 40 A randomized controlled trial found that whereas a nonopioid group had significantly greater VAS pain on postoperative days 1 and 4 after ARCR, the nonopioid group actually demonstrated significantly lower VAS pain and pain intensity at every time point (P \ .01) when accounting for confounding factors. 17 Moutzouros et al 26 found that 45% of patients were able to complete nonopioid postoperative protocols when enrolling patients undergoing a wide range of sports orthopaedics procedures, including anterior cruciate ligament reconstruction, ARCR, labral repair, and meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several prospective studies have investigated the feasibility of opioid-free postoperative protocols after ARCR as well as for other common sports orthopaedic procedures. 17,26,40 The Cannabis sativa plant is a promising alternative for augmented pain control, with its derivative cannabinoids, namely cannabidiol (CBD), the subject of increased investigation. While there is growing evidence from in vitro and animal studies for CBD as a pain modulator, 2,9,14,16,25,44,48 there remains a lack of high-quality evidence in orthopaedics with respect to CBD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of dexmedetomidine-based anesthesia leverages the benefits of the multimodal pain control strategy in the perioperative arena to decrease both peripheral and central sensitization [ 11 ]. Notably, this new modality of general anesthesia has been shown to significantly reduce opioid consumption in patients undergoing bariatric surgery [ 12 ], pancreatic surgery [ 13 ], major urological procedures [ 14 ], rotator cuff repair [ 15 ], and total hip replacement [ 16 ]. A recent randomized controlled trial in gynecological surgery furthermore corroborated that opioid-free anesthesia was associated with significant improvement in postoperative analgesia, compared to traditional opioid-based anesthesia [ 17 ].…”
mentioning
confidence: 99%